2019
DOI: 10.29309/tpmj/2019.26.07.2631
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Ophthalmic Medicolegal Cases Presenting to Tertiary Care Hospital.

Abstract: Objectives: To study the etiology and visual acuity profile of ophthalmic medicolegal cases presenting to a tertiary care hospital. Study Design: Retrospective study. Setting: Lahore General Hospital, Lahore. Period: 1-3-2017 to 30-10-2018. Methodology: This retrospective study was conducted after taking ethical approval from the institutional review board. Record of medicolegal cases presenting during the study period were studied and assessed. In this study, etiology of trauma inflicted to eye and visual acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Similar results were reported by Baig R et al, which also reported high incidence of eye injuries among male patients in Karachi 14 . Amjad et al had also reported 65% male patients with trauma in their study 8 . In the study by Timsinha et al, 69.32% were males 13 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Similar results were reported by Baig R et al, which also reported high incidence of eye injuries among male patients in Karachi 14 . Amjad et al had also reported 65% male patients with trauma in their study 8 . In the study by Timsinha et al, 69.32% were males 13 .…”
Section: Discussionmentioning
confidence: 62%
“…They presents at varying time interval of the trauma, which may be weeks or days. It is the duty of a designated doctor to ascertain realistic and actual assessment of injuries by a careful history and thorough examination 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It becomes the liability of the reporting doctor to make realistic and accurate assessment of injuries by careful history and thorough examination. [ 7 ] In circumstance of COVID era, restriction of public transport and fear of getting infected with serious illness are possible factors of presenting late for medicolegal implication. Accurate description, interpretation, and documentation of injuries are most important function of attending doctor to ensure patient gets every opportunity to maximize legal and health-care outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Patients with medicolegal implications come to an ophthalmologist for examination at varying time intervals of trauma infliction. [ 7 ] This requires a careful history and thorough examination to ascertain the actual and realistic estimation of injuries. [ 8 ] These patients may feign injuries to deliberately mislead the doctor to make a wrong diagnosis for compensation purposes.…”
Section: Introductionmentioning
confidence: 99%